(untitled) (REICE: Revista Electrónica de Investigación en Ciencias Económicas, 2024)
This article analyzes the challenges and opportunities faced by rural agroindustrial companies in Nicaragua, highlighting the importance of innovation and the promotion of innovative ventures to promote sustainable growth in this strategic productive sector. Through descriptive analysis, the article identifies the prevailing obstacles and promising avenues to promote progress and overcome challenges, which could be leveraged for further development of agribusiness in rural areas. An investigation is carried out on the current problems and potential solutions that contribute to boosting agriculture and industry. This article is based on conducting surveys with a number of 138 protagonists of the National Fair Park, who have received technical assistance to improve the presentation and quality of their products. One of the main findings highlights the importance of government support and continuous training to strengthen administrative skills and market strategies. The strategic creation of this promotion and marketing space has provided an effective platform to establish direct marketing of products, benefiting small and medium producers. Likewise, the need for more rigorous institutional monitoring and continuous attention to guarantee the sustainability of rural agroindustries is highlighted. In addition to maintaining and expanding training programs as an integral part of the sector’s development strategies.